Fostering musical independence in students by teaching rhythmic accuracy using the curriculum Teaching rhythm logically - Stufflebeam, Meagan (Kansas State University, 2023)
The following lessons will focus on teaching using the methods in Teaching Rhythms Logically (Potter Williams, 2016). This method uses the Eastman counting system with the breath impulse subdivision of the eighth note. Before teaching the students this method, they took a written pre-test and participated in an informal group aural assessment. As each class encountered new material, students used the following approach to learning new rhythmic and melodic passages alike: they would count the example, say or sing the selection using a "ta" syllable, practice the example by blowing air through the instrument but not creating a sound (also known as air playing), and finally play the example on instruments with full sound. Through this process, the goal was to see improvement in rhythmic accuracy and sight-reading ability. This method helped the students become more independent, assisted them in learning new passages and performed with more rhythmic stability and confidence. Upon completion of Teaching Rhythm Logically (Potter Williams, 2016), students took a written post-test and participated in an informal aural assessment to address whether there was an improvement in rhythmic accuracy.
Keywords: Rhythm; Teaching rhythms logically; Eastman counting method; Social-emotional learning